The influence of institutional logics on CSR in China: the case of Chinese international shipping - Shen, Xi (2021)
Taking the Chinese international shipping as an example, this thesis investigates how institutional logics influence the nature of Corporate Social Responsibility (CSR) in China, i.e., the way CSR is interpreted, the focus issues of CSR and the practice of CSR in China, A multi-level analysis is conducted at societal, field, and organizational levels. At societal level, how the role of CSR in Chinese state logics has evolved over time is reported. At field level, how the nature of CSR in the Chinese international shipping field has evolved over time is considered. Finally, at organizational level, how Chinese international shipping companies perceive and practice CSR is discussed.